The fellowship of the ring, The lord of the rings part 2 - Tolkien, J. R. R. (HarperCollins , London, 2012)
The 'Fellowship of the Ring' is the first part of Tolkien's epic adventure 'The Lord of the Rings'. Frodo Baggins finds himself faced with an immense task, as his elderly cousin Bilbo entrusts the Ring to his care